Peran Perceived Organizational Support dan Work-Life Balance Terhadap Intention To Stay: Mediasi Komitmen Organisasional - Joenanika Azzahroina Albensia; Fitri Wulandari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the relationship between perceived organizational support and work-life balance on intention to stay with organizational commitment as a mediating variable. This study uses a quantitative medote with purposive sampling technique involving 146 respondents from employees of manufacturing companies in the basic and chemical industry sector in Sragen. Data collection was done through questionnaires, and data analysis using SmartPLS 3.0. The results showed that perceived organizational support and work-life balance have a positive and significant effect on intention to stay. In addition, both variables also have a positive effect on organizational commitment, which in turn contributes to intention to stay. Mediation analysis confirmed that organizational commitment mediates the relationship between perceived organizational support and work-life balance on intention to stay. This study shows that organizational support and work-life balance are important to keep employees stay. The implication of this study confirms that companies should implement policies that support work-life balance and strengthen employee commitment to increase workforce retention.